Network disruption detected in PG (Papua New Guinea) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Papua New Guinea. Data sourced from IODA.
Network Disruption Incident ID: PG-2026-0001. Severity: critical. Confidence: 70%